WEBSITE VIRTUAL REALITY WISATA JERON BETENG - Andi Haryanto (DeKaVe, 2011)
Virtual Reality Website of Jeron Beteng is an effort task to make virtual visualization of Jeron Beteng with its heritage and social cultural life of the people who lived surround it as an object. The visualized element of Virtual Reality Website of Jeron Beteng is an interactive broadcast of photographical view of specific locations in Jeron beteng area with 3600 widely views. The user of this website can see and twist the unlimited angle of a photo object, it can be twist whether from right to left orup and down, and zoom in or zoom out the appearance of the tourist object photos in the area of Jeron Beteng. The user also can move from one location to another location only by click, so they can feel the sensation of their presences in that location. Virtual Reality Website of Jeron Beteng has some superior aspects like in multimedia contents, the complete information of Jeron Beteng tourism activities, and designed as an artificial object. This website is created as a media to recognize the potential of Jeron Beteng as a tourist object. The expected effect of this website is to make tourist more curious and motivated them to come and see directly the atmosphere of Jeron Beteng itself, because virtual visualization can't replaced the sensation of being in the location.Keywords : Website, Virtual Reality and Jeron Beteng